(untitled) («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
Development of auditory skills in children learning a foreign language is a process of great importance for their future. This process takes place at different stages in each child. It depends on their psychology and the education they receive in the educational institution. In this article, we have described in detail the advantages and methods of developing the hearing ability of students.